2012
DOI: 10.1038/icb.2012.43
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous, TAP‐independent lysosomal presentation of a respiratory syncytial virus CTL epitope

Abstract: Respiratory syncytial virus causes lower respiratory tract infections in infancy and old age, affecting also immunocompromised patients. The viral fusion protein is an important vaccine candidate eliciting antibody and cell-mediated immune responses. CD8 þ cytotoxic T lymphocytes (CTLs) are known to have a role in both lung pathology and viral clearance. In BALB/c mice, the fusion protein epitope F249-258 is presented to CTLs by the murine major histocompatibility complex (MHC) class I molecule K d . In cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 28 publications
2
3
0
Order By: Relevance
“…Interestingly, unlike HSV-1 gB, Tey et al hypothesize that pUL138 degradation and subsequent generation and loading of the peptide into MHCI occurs in the autophagolysosome, where antigen does not access to the cytosol. A similar pathway of MHCI antigen presentation has also been described for an epitope derived from respiratory syncytial virus, where MHCI antigen presentation was abrogated in the presence of 3-MA treatment (Johnstone et al, 2012). Therefore autophagy-mediated MHCI presentation is a relevant pathway of antigen presentation for several virus-associated antigens and may, or may not, involve the classical MHCI antigen presentation route.…”
Section: Autophagy In Classical Mhc Class I Antigen Presentationsupporting
confidence: 55%
“…Interestingly, unlike HSV-1 gB, Tey et al hypothesize that pUL138 degradation and subsequent generation and loading of the peptide into MHCI occurs in the autophagolysosome, where antigen does not access to the cytosol. A similar pathway of MHCI antigen presentation has also been described for an epitope derived from respiratory syncytial virus, where MHCI antigen presentation was abrogated in the presence of 3-MA treatment (Johnstone et al, 2012). Therefore autophagy-mediated MHCI presentation is a relevant pathway of antigen presentation for several virus-associated antigens and may, or may not, involve the classical MHCI antigen presentation route.…”
Section: Autophagy In Classical Mhc Class I Antigen Presentationsupporting
confidence: 55%
“…While, however, HSV gB processing was still proteasome dependent, HCMV pUL138 degradation was proteasome independent, suggesting that maybe an endosomal MHC class I loading compartment requires macroautophagy for its formation, and can receive input from lysosomal or proteasomal antigen processing. Supporting this notion is the recent finding that crosspresentation of the F protein of the respiratory syncytial virus (RSV) also requires macroautophagy, but is independent of TAP and proceeds via lysosomal degradation [35].…”
Section: Contribution Of Autophagy To Mhc Class I Antigen Presentationsupporting
confidence: 49%
“…Moreover, α‐Al 2 O 3 ‐OVA complex co‐localized with LC3 in DCs suggesting that autophagy can potentiate cross‐presentation of antigens by DCs through their targeting to autophagosomes. A study using respiratory syncytial virus (RSV) suggested that autophagy and lysosomal degradation are required for cross‐presentation of an RSV‐derived epitope by MHC I using a lymphoblastoid cell line deficient in TAP . Interestingly, results from Knittler and colleagues showed that autophagy targets intracellular Chlamydia during DC maturation after infection and that autophagic processing is necessary for Chlamydia epitope presentation onto MHC I .…”
Section: Autophagy and Cross‐presentationmentioning
confidence: 99%